Tartaric acid-assisted precipitation of visible light-driven Ce-doped ZnO nanoparticles used for photodegradation of methylene blue - Surisa Sa-nguanprang (2020)
© 2020, Australian Ceramic Society. ZnO nanoparticles doped with different contents of Ce were synthesized by a tartaric acid-assisted precipitation method. The as-synthesized samples with and without high temperature calcination were characterized by CHNS/O analysis, thermogravimetric analysis (TGA), X-ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and UV-visible spectroscopy. According to the analytical results, the as-synthesized undoped and Ce-doped ZnO samples were pure phase of hexagonal ZnO. The Ce-doped ZnO nanoparticles were much smaller than the pure ZnO nanoparticles, with 117 ± 37 nm for undoped ZnO and 18 ± 4 nm for 5 wt% Ce-doped ZnO. The as-synthesized samples were evaluated through the photodegradation of methylene blue (MB) under visible light irradiation. The 5 wt% Ce-doped ZnO nanoparticles exhibited the best photocatalytic activity with 95.2% within 60 min, and the degraded products were detected by direct mass spectrometry. A mechanism for photocatalysis of Ce-doped ZnO nanoparticles was also proposed.